ANALISA AERODINAMIK, STRUKTUR, FLIGHT DYNAMIC AND PERFORMANSI UCAV (UNMANNED COMBAT AIR VEHICLE) - Rosihan Ramin; Heriana Heriana; Bondan Tiara Sofyan; Mas Ayu Elita Hafizah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
PTTA (Unmanned Aircraft) is also used to support national security and reconnaissance, making it easier for the TNI to work and simultaneously saving the cost of monitoring Indonesian territories. This study will produce design details, design analysis with design configuration requirements from UCAV (Unmanned Combat Air Vehicle), which has Weight and Balance with a two-point landing case so that UCAV is declared safe to receive maximum load loads and flutter analysis shows that the vehicle does not occur. Flutter phenomenon up to a speed of 150 KTAS meets the requirements of aeroelastic flutter based on the rules set by CASR (Civil Aviation Safety Regulations) 23 and IMA (Indonesian Military Airworthiness). From the identification of DR&O (Design Requirements and Objectives) and Initial Sizing, there is an effect of airflow and angle of attack on UCAV on aerodynamic characteristics, used as contours of pressure and temperature on the body and vector for UCAV body velocity. Pressure contours, temperature contours, and velocity vectors on the UCAV so that the analysis in determining the performance of the aircraft is representative following CASR regulations 23 and 24